The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1016/j.cardfail.2007.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Association of Diurnal Blood Pressure Pattern With Risk of Hospitalization or Death in Men With Heart Failure

Abstract: In addition to other traditional predictors, BP dipping status may be an important prognostic factor in HF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 37 publications
(7 reference statements)
0
19
0
1
Order By: Relevance
“…This is not consistent with the previous report in which the riser BP pattern was associated with adverse outcome in HFrEF. 8 This difference can be explained by the difference in HF severity. The percentage of NYHA III/IV HF patients in that study was greater than in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is not consistent with the previous report in which the riser BP pattern was associated with adverse outcome in HFrEF. 8 This difference can be explained by the difference in HF severity. The percentage of NYHA III/IV HF patients in that study was greater than in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…7 Although a single report showed that the riser BP pattern was associated with adverse prognosis in HFrEF patients, 8 the clinical significance of abnormal circadian BP rhythm has not been established in patients with HF. Thus, we tested the hypothesis that the riser BP pattern is associated with adverse outcome in HF patients, especially those with HFpEF, by conducting an analysis of the database of the updated hospital HF cohort at Jichi Medical University Hospital.…”
mentioning
confidence: 99%
“…Pronounced circadian variation has been demonstrated for CPE occurrence and a casual relationship with hypertension, particularly with nondipper/riser profile and with the presence of excessive morning surge. (22,23) Moreover, our results indicate that the chronobiological approach may be considered even beyond the horizon of the twenty four hour cycle. Although the causal relationship between gravitational interaction between the Earth and the Moon and the occurrence of CPE has not been detected so far, it is easy to automatically calculate the periods with increased risk of CPE occurrence in advance.…”
Section: Discussionmentioning
confidence: 69%
“…In addition, the serum creatinine level and the 24 h U-NE level were independent determinants of nighttime BP decline. Although the abnormal circadian BP pattern was reported as a prognostic predictor in the general population or in patients with hypertension or ischemic heart disease [10,11,12,22,23], to our knowledge, this is the first report of the prognostic value of circadian BP profile in patients with NIDCM.…”
Section: Discussionmentioning
confidence: 97%